Appraising weak and strong sustainability: searching for a middle ground - Davies, George Randal (Consilience, 2013)
This paper seeks to address the ongoing issue of weak and strong sustainability, searching for a middle ground. It discusses the differences between weak and strong sustainability arguing for equality and equity between nature and humankind though movement towards an eco-socio-feminist perspective as an idealist point of view. Through this, full equality and balance may be attained.